Effects of a Trans-Theoretical Model-Based Health Education Program on the Management of Cognitive Dysfunction in Older Adults With Mild Cognitive Impairment: Study Rationale and Protocol Design for a Randomized Controlled Trial - Liu, Xiaoshen; Wang, Lina; Tao, Hong; Ge, Chenxi; Zhen, Xueting; Sun, Xue; Wang, Simeng; Su, Liming (Frontiers in Psychiatry, 2021)
Introduction: Recent studies have confirmed that management/intervention of cognitive dysfunction gains considerable positive effects in individuals with mild cognitive impairment (MCI), but older adults with MCI are generally scant of compliance of participation in various cognitive dysfunction management/intervention strategies. While health education programme can effectively improve the level of knowledge disease, whether health education programme is sufficient to promote behavior change of older adults with MCI in the community is unknown. Objective: The study aims to assess the relationships of a health education programme based on the trans-theoretical Model (TTM) with the level of compliance of participation in cognitive dysfunction management, disease knowledge and other cognition-related health outcomes (general cognitive function, sleep quality, depression symptoms) for older adults with MCI. Methods: This programme is a single-blinded, randomized, prospective clinical trial. 132 participants with MCI will be recruited and randomly assigned to the TTM-based health education group (intervention group) and standard health education (control group) at a ratio of 1:1. The intervention group will receive a TTM-based health education programme for 45-60 min, one time a week for eight weeks, while the control group will receive standard health education. Assessors blinded to participant allocation will conduct baseline, post-intervention, and 3-month follow-up assessments. Statistical analyses will consist of the Wilcoxon test, Chi-square test, T-test, 2 (group) × 3 (time) ANOVA with a 5% cut-off for significance. Discussion: Suppose the TTM-based health education programme would provide validated community-based cognitive dysfunction management strategies for older adults with MCI. It would be a potential approach to improve participation in cognitive dysfunction management and cognition-related health outcomes.